A Supplementary Note on Mr Pearce's General Equilibrium Model - Ozga, S. A. (Review of Economic Studies, 1957)
Journal Article A Supplementary Note on Mr Pearce's General Equilibrium Model Get access S. A. Ozga S. A. Ozga London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 25, Issue 1, October 1957, Pages 62–63, https://doi.org/10.2307/2296125 Published: 01 October 1957